Topographical Organization of Motor Neurons of the Ulnar and Radial Nerves in Albino Rat: A Retrograde Hoseradish Peroxidase (HRP) Study - Saeed, Muhammad; Janjua, Zahoor (Journal of Postgraduate Medical Institute, 2011)
The somatic motor neurons in the ventral horn of the spinal cord are structures of vital importance fro they and their axons constitute the final common pathway to the voluntary muscles of the trunk and limbs. These motoneutrons do not form an indiscriminate mass but are rather groupsed together in relatively discrete longitudinal columns. Thus a knowledge of their distribution and somatotopic organization with respect to muscles and nerves has attracted the attention of many investigators. The majority of earlier investigations into the problem of motoneuronal localization done before 1971 utilied the unreliable retrgrade degeneration method however, in 1971 an entirely new te3chnuqe, based on retrograde intra axonal transport of horse was clearly demonstrated that HRP may be transported retrogradely from a muscle to neurons supplying it. Since then studies on localization of neurons supplying a muscle or forming a nerve gathered monentum using HRP as neuronal marker.